Analisis Penstabilan Tegangan Output Generator Induksi 3 Fasa - Rachmat Sucipto; Tresna Umar Syamsuri; Epiwardi (Politeknik Negeri Malang, 2023)
One of the alternative generators in supplying electrical energy is a 3-phase generator made from a 3-phase slip ring induction motor, after which the rotor winding is supplied with a DC source and rotated using a prime mover. The problem arises because of the large % voltage regulation of a 3-phase generator when it is under load. This is because the induction generator has a relatively larger voltage loss when loaded with a certain load compared to a 3-phase synchronous generator. To overcome these conditions, there are several ways that can be used to stabilize the voltage from the generator, namely: setting the excitation current from the generator, setting the connection on the rotor windings (using 2 windings or using 3 rotor windings) and a combination of the two steps above. . Based on the results of experiments that have been carried out, it is known that the method of stabilizing the output voltage by setting the rotor winding connection is less effective than setting the excitation current because it turns out that the results of changing the output voltage are not too significant compared to changing the generator excitation current. In addition, it is also known that the stabilization of the output voltage from an inductive load will require a DC voltage that is greater than when under a resistive load because of the large difference in losses.